Development of an Integrated Religious Biotechnology Textbook - Khosi'in; Nur Hidayat; Azizah Aryati; Zulfikri Muhammad (Postgraduate, University of Mataram, 2023)
This research aims to produce textbooks that are integrated with Islamic religious values. This type of research uses RnD development research with the ADDIE development model, the instrument used is a feasibility questionnaire for religious material experts, biotechnology material experts, media experts, language experts and a user response questionnaire totaling 27 respondents consisting of 3 lecturers and 24 students. The research results show feasibility religious material expert 84.70%, biotechnology material expert eligibility 100%, language expert eligibility 88.67% and media expert eligibility 83.30%, while user response test results with a value of 91.10% show that the textbook developed is a book teaching biotechnology integrated with Islamic religious values is very precise, very appropriate, very clear, very interesting and very easy for students to understand.